Unemployment of Immigrants in European Union - Malačič, Janez (Anali PAZU, 2022)
Future immigration in Europe will mark many characteristics of European societies. However, the most important characteristic of immigrants' integration will be their employment and economic activity. Immigrants in European Union have frequently faced numerous obstacles to the integration in the host societies as well as higher unemployment than natives. The author analyses Eurostat's labour force survey data base and extracts information on unemployment of immigrants in the EU. In spite of some data problems the results show higher unemployment of immigrants than in the case of natives. Immigrants born in non-EU countries are especially vulnerable.
Keywords: immigration; labour market; unemployment; European Union